Multi-Objective Swarm Intelligent Systems Theory & Experiences - Coelho, Leandro dos Santos (Studies in Computational Intelligence,, 2010)
The editors of this volume, Nadia Nedjah, Leandro dos Santos Coelho and Luiza de Macedo Mourelle, have done a superb job of assembling some of the most innovative and intriguing applications and additions to the methodology and theory of multi-objective swarm intelligence - the immitation of social swarms behaviors for the solution of optimization problems with respect to many criteria.